Field evaluation of the bioefficacy of diflubenzuron (Dimilin (R)) against container-breeding Aedes sp mosquitoes - Chen, C.D.; Seleena, B.; Chiang, Y.F.; Lee, H.L. (2008)
The inhibitory activity of diflubenzuron, a chitin synthesis inhibitor, on the ecdysis of Aedes sp. larvae was evaluated in earthen jars and automobile tires. Two formulations of diflubenzuron were used in this study: Dimilin (R) WP (wettable powder), 25 and Dimilin (R) GR (granular), 2. The equivalent rate of 25 g/ha, 50 g/ha and 100 g/ha active ingredients for both WP and GR formulations were used in this study. Generally, at the higher dosage of 100 g/ha, both formulations were more effective against Aedes mosquitoes. On the whole, the WP formulation appeared to perform better than the GR formulation in terms of residual activity.